2011
DOI: 10.1152/ajpcell.00379.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Ca2+ signaling in astrocytes from mice lacking amyloid precursor protein

Abstract: The relationship between altered metabolism of the amyloid-β precursor protein (APP) and Alzheimer's disease is well established but the physiological roles of APP still remain unclear. Here, we studied Ca(2+) signaling in primary cultured and freshly dissociated cortical astrocytes from APP knockout (KO) mice and from Tg5469 mice overproducing by five- to sixfold wild-type APP. Resting cytosolic Ca(2+) (measured with fura-2) was not altered in cultured astrocytes from APP KO mice. The stored Ca(2+) evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 83 publications
(118 reference statements)
4
45
1
Order By: Relevance
“…In hippocampal astrocytes isolated and cultured from neonatal 3xTg-AD mice, the amplitude of ATP-induced [Ca 2+ ] i transients as well as the store-operated Ca 2+ entry were significantly increased [125,137]. In contrast, store-operated Ca 2+ entry in astrocytes from APP-over-expressing Tg5469 AD mice was not affected, although the deletion of APP inhibited SOCE, possibly due to down-regulation of Orai1 and TRPC1 channels [142].…”
Section: Ca 2+ Signalling In Ad Astrocytesmentioning
confidence: 91%
“…In hippocampal astrocytes isolated and cultured from neonatal 3xTg-AD mice, the amplitude of ATP-induced [Ca 2+ ] i transients as well as the store-operated Ca 2+ entry were significantly increased [125,137]. In contrast, store-operated Ca 2+ entry in astrocytes from APP-over-expressing Tg5469 AD mice was not affected, although the deletion of APP inhibited SOCE, possibly due to down-regulation of Orai1 and TRPC1 channels [142].…”
Section: Ca 2+ Signalling In Ad Astrocytesmentioning
confidence: 91%
“…[Ca 2ϩ ]cyt was measured with fura-2 using digital imaging (25). Mouse embryonic fibroblasts or Neuro 2A cells were loaded with fura-2 by incubation for 35 min in culture medium containing 3.3 M fura-2 AM (20 -22°C, 5% CO2-95% air).…”
Section: Methodsmentioning
confidence: 99%
“…Image acquisition and analysis were performed with a MetaFluor/MetaMorph Imaging System (Molecular Devices, Downingtown, PA). [Ca 2ϩ ]cyt was calculated by determining the ratio of fura-2 fluorescence emission (510 nm) excited at 380 and 360 nm, as previously described (25). Intracellular fura-2 was calibrated in situ separately in cultured mouse embryonic fibroblasts and Neuro 2A cells (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered Ca 2+ homeostasis has been also linked to neuronal damage caused by brain aging or Alzheimer's disease. A recent study suggested that the physiological role of amyloid-b precursor protein (APP), whose altered metabolism has been associated with Alzheimer's disease, is the regulation of TRPC1/Orai1-mediated SOCE which is critical for Ca 2+ signaling in astrocytes [ 253 ] . In line with this report, impaired SOCE was also observed in fi broblasts bearing mutated presenilin-1 and 2 genes, which has been associated to autosomal dominant familial Alzheimer's disease (FAD), while absence of this protein led to increased SOCE and augmented expression of STIM1 [254][255][256][257] .…”
Section: Soce and Diseasementioning
confidence: 99%